Undergraduate Medical education in Nepal: Need for Change - Shah, Nabina (Journal of Kathmandu Medical College, 2016)
Not available.Journal of Kathmandu Medical College, Vol. 4, No. 1, Issue 11, Jan.-Mar., 2015